2015
DOI: 10.1002/adma.201503336
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic Construction of Plasmonic Heterostructures in Well‐Organized Arrays for Nanophotonic Materials

Abstract: Plasmonic heterostructures are deterministically constructed in organized arrays through chemical pattern directed assembly, a combination of top-down lithography and bottom-up assembly, and by the sequential immobilization of gold nanoparticles of three different sizes onto chemically patterned surfaces using tailored interaction potentials. These spatially addressable plasmonic chain nanostructures demonstrate localization of linear and nonlinear optical fields as well as nonlinear circular dichroism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…The ability to assemble such plasmonic structures on patterned brushes allows for investigating the structure property relations at the single particle level and offers unprecedented capabilities in fabrication of devices. [13][14][15] A variety of different approaches including electronbeam lithography, dip-pen nanolithography and self-assembly has been used to fabricate nanoscale patterns of polymer brushes. [16][17][18][19][20][21][22] Advanced lithography techniques are highly developed and allow for fabrication of polymer brushes with high levels of resolution and fidelity; however, these techniques typically require high capital and operation costs, and not suitable for some of the emerging applications where there is a need for patterning unusual materials and substrates which, for example, are nonplanar and flexible.…”
Section: Abstract: Nanofabrication Polymer Brushes Electrospinningmentioning
confidence: 99%
“…The ability to assemble such plasmonic structures on patterned brushes allows for investigating the structure property relations at the single particle level and offers unprecedented capabilities in fabrication of devices. [13][14][15] A variety of different approaches including electronbeam lithography, dip-pen nanolithography and self-assembly has been used to fabricate nanoscale patterns of polymer brushes. [16][17][18][19][20][21][22] Advanced lithography techniques are highly developed and allow for fabrication of polymer brushes with high levels of resolution and fidelity; however, these techniques typically require high capital and operation costs, and not suitable for some of the emerging applications where there is a need for patterning unusual materials and substrates which, for example, are nonplanar and flexible.…”
Section: Abstract: Nanofabrication Polymer Brushes Electrospinningmentioning
confidence: 99%
“…This architecture was fabricated through chemical pattern directed assembly 35 of NDs on a silicon substrate, followed by transfer printing 36 with PDMS as described in Supplementary Note 1. This portable and reusable system allows us to control the position of the NDs with respect to the MSLs and to easily locate and address single nanoparticles, which is critical for performing our measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting structures are extremely interesting with a high‐level of control over the separation distances between the individual NPs; however, inherent challenges exist in the high‐yield generation of such structures over large areas on surfaces of relevant substrates in a dried state that are suitable for device applications. A highly promising strategy that can overcome these challenges is the assembly of heterostructures directly on the surface of substrates by immobilization of colloidal NPs . This strategy has the advantage of direct integration of heterostructures on the relevant substrates from colloidal NPs that are available in massive quantities with precisely defined size, shape, surface roughness and crystallinity.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy has the advantage of direct integration of heterostructures on the relevant substrates from colloidal NPs that are available in massive quantities with precisely defined size, shape, surface roughness and crystallinity. We previously showed that chemical nanopatterns fabricated using electron beam lithography allowed for directed assembly of colloidal gold NPs to fabricate single heterostructures with precise control over their positions. The serial nature of electron beam lithography together with its high cost hinder the use of such substrates in practical applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation